MBNQA criteria in education: assigning weights from a Malaysian perspective and proposition of an alternative evaluation scheme - Islam, Rafikul (IFORS (The International Federation of Operational Research Societies), 2007)
In order to improve quality and productivity among American companies, Malcolm Baldrige National Quality Award (MBNQA) was launched by the National Institute of Standards and Technology (NIST) under the Department of Commerce of US government in 1987. Over the years, the award has been proved to be effective in improving companies’ market share, customer satisfaction, employee morals and also profitability. MBNQA has been a ‘role model’ in developing national quality award for many other countries in the world. Furthermore, for organizational self-assessment, the criteria framework of MBNQA has been in use throughout the world. Presently, the award is offered in three categories: Business, Education, and Health-care. The present paper is concerned with MBNQA in Education. NIST has developed a comprehensive set of criteria to be fulfilled in order to be eligible to win the award. However, in the existing literature, it is not clear how the weights are assigned to the criteria and subcriteria. The present paper uses analytic hierarchy process (AHP) to reassign criteria weights from a Malaysian perspective. Furthermore, the paper points out the fallacy of the present evaluation scheme and proposes an alternative one based upon the absolute measurement procedure of AHP. The modified scheme is expected to enhance the fairness in evaluation of the award aspirants. The paper also shares the experiences gathered in data collection using AHP.